WLT, a radio romance - Keillor, Garrison (New York : Viking, 1991)
The novel upon which Keillor has worked over the last 15 years. A treasure for his myriad fans.
Also issued online.
Keywords: Radio personalities -- Minnesota -- Fiction; Minnesota -- Fiction; Humorous stories; Radio stations -- Fiction; Minnesota -- Fiction; Brothers -- Fiction